Epidemiological, clinical, and immunological features of a cluster of COVID-19–contracted hemodialysis patients (2020)
Background: The outbreak of highly contagious coronavirus disease 2019 (COVID-19) has posed a serious threat to human life and health, especially for those with underlying diseases. However, the impact of COVID-19 epidemic on hemodialysis (HD) centers and HD patients has not been reported. Methods: We reviewed the whole course of the COVID-19 in the HD center of Renmin Hospital, Wuhan University (from January 14, 2020, to March 12, 2020). We compared the clinical manifestation and immune profiles among different patient groups with healthy individuals. Results: Forty-two of 230 HD patients (18.26%) and 4 of 33 medical staff (12.12%) were diagnosed with COVID-19 during the study period. Fifteen HD patients (6.52%), including 10 COVID-19 diagnosed, died. Only 2 deaths of the COVID-19 HD patients were associated with pneumonia/lung failure, others were ascribed to cardiovascular/cerebrovascular diseases or hyperkalemia. Except for 3 patients who were admitted to the intensive care unit for a severe condition (8.11%), including 2 who died, most COVID-19 diagnosed patients presented mild or nonrespiratory symptoms. The flow cytometric analysis of peripheral blood showed that multiple lymphocyte populations in HD patients were significantly decreased. HD patients with COVID-19 even displayed more remarkable reduction of serum inflammatory cytokines than other patients with COVID-19. Conclusions: Compared with the general population, HD patients and health care professionals are the highly susceptible population and HD centers are high-risk areas during the outbreak. Most HD patients with COVID-19 exhibited mild clinical symptoms and did not progress to severe pneumonia, likely due to the impaired cellular immune function and incapability of mounting cytokine storm. More attention should be paid to prevent cardiovascular events, which may be the collateral impacts of the COVID-19 epidemic on HD patients.